Beneath and beyond the Chinese miracle - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2011)
China’s rapid economic growth has masked a worrying trend that personal income growth is falling increasingly behind. If this is not addressed, China will remain stuck to its export-driven model. Huang Yasheng, a professor at Massachusetts Institute of Technology and SMU's Ho Bee Professor in Chinese Economy and Business, believes that the country’s leaders need to figure out how to boost personal income and domestic consumption, and not focus simply on gross domestic product.